Analysis of Drosophila salivary gland, epidermis and CNS development suggests an additional function of brinker in anterior-posterior cell fate specification. - Lammel, U.; Meadows, L.; Saumweber, H. (Mechanisms of Development, 2000)
Salivary glands are simple structured organs which can serve as a model system in the study of organogenesis. Following a large EMS mutagenesis we have identified a number of genes required for normal salivary gland development. Mutations in the locus small salivary glands-1 (ssg-1) lead to a drastic reduction in the size of the salivary glands. The gene ssg-1 was cloned and subsequent sequence and genetic analysis showed identity to the recently published gene brinker. The salivary gland placode in brinker mutants appears reduced along both the anterior-posterior and dorso-ventral axis. Analysis of the brinker cuticle phenotype revealed a similar loss of anterior-posterior as well as lateral cell fates. The abdominal ventral denticle belts show a reduced number of setae in the first denticle row. Furthermore, we observed a preferential loss of lateral neuroblasts in the anterior parasegment. Together, these phenotypes suggest that brinker not only plays a role in dorso-ventral but also in anterior-posterior axis patterning.